The Effects of Angiotensin Metabolites on the Regulation of Coagulation and Fibrinolysis in Cultured Rat Aortic Endothelial Cells - Nishimura, Hiromi; Tsuji, Hajime; Masuda, Haruchika; Kasahara, Teruhisa; Yoshizumi, Masami; Sugano, Tatsuya; Kimura, Shinzo; Kawano, Hidehiko; Kunieda, Yasufumi; Yano, Shingo; Nakagawa, Katsumi; Kitamura, Hidetsugu; Nakahara, Yoshifumi; Sawada, Shohei; Nakagawa, Masao (Thrombosis and Haemostasis, 1999)
Not only angiotensin II (Ang II) but also other angiotensin metabolites such as angiotensin I (Ang I), angiotensin III (Ang III), angiotensin IV, or angiotensin 1-7 have recently been reported to have various activities. Few data, however, are available on the regulation of thrombus formation. In this study, we investigated the effects of angiotensin metabolites on the mRNA expression of tissue factor (TF), tissue factor pathway inhibitor (TFPI), plasminogen activator inhibitor-1 (PAI-1), and tissue type plasminogen activator (TPA) in cultured rat aortic endothelial cells. None of the used angiotensin metabolites altered TFPI or TPA mRNA expression levels. Ang I, Ang II, and Ang III made TF and PAI-1 mRNA inductions which were inhibited by an selective antagonist of angiotensin II type 1 receptors. These metabolites made TF predominant to TFPI or PAI-1 to TPA, and could render endothelial cells thrombogenic.
Keywords: Angiotensin; thrombosis; fibrinolysis; tissue factor; plasminogen activator inhibitor 1